The Contractor's Insolvency, Grounds for Amending the Public Procurement Contract - Ecaterina Milica DOBROTA; Roxana SARBU; Silvius STANCIU (Communications of International Proceedings, 2022)
The public procurement contracts, with their high values and quantities, attract many companies to compete in the market economy. Although public authorities use efficient selection criteria to identify the most competitive economic operator, in the execution of the contract, the company may become insolvent or even bankrupt. For the contract to continue, the contracting authority's priority must be to replace the winning bidder (which has become bankrupt), while respecting the competitive environment. The contract amendment is a challenge for both the contractor and the beneficiary if we take into account the summary legal provisions of the Directive no. 24/2016 regarding the public procurement. Based on cases registered at the Court of Justice of the European Union, this study analyses the necessary conditions for contract amendment and proposes steps that should be taken to replace the original contract in case of insolvency/bankruptcy. The aim of this study is to assist public procurement specialists in understanding how to replace the bankrupt contractor.
Keywords: public procurement; insolvency; contract amendment; Romania.